Adoption of Mobile Learning at Universities Using the Extended Technology Acceptance Model - Misbahul Aziz; Edwin Pramana; Hartarto Junaedi (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2022)
This study aims to contribute to the proof of factors likely to determine the success of M-learning adoption based on previous research.  This is done because there are many different theoretical models proposed.  However, there is not yet a model that can be generally accepted as an established theoretical model for the adoption of M-learning in universities.  This research is expected to make a significant contribution to the development of a better theoretical understanding of the determinants that influence the adoption of M-learning using the Technology Acceptance Model (TAM).  To collect the data, researchers distributed questionnaires to respondents using google forms.  Forms are distributed via WhatsApp and Telegram.  The data used was 515 M-learning users.  Theoretical model research was carried out with Structural Equation Model (SEM) analysis, then SPSS and Amos as support for analysis.  There are six factors that determine the results of acceptance of M-leaning adoption in this study, namely Social Influence, Perceived Enjoyment, Facilitating Condition, Self-Efficacy, Perceived Usefulness, and Perceived Ease of Use.  The five factors that show positive and significant relationships are Social Influence, Perceived Enjoyment, Self-Efficacy, Perceived Usefulness, and Perceived Ease of Use.  Perceived Usefulness has the first strongest positive and significant value, and then Social Influence has the second strongest value.  Each factor has a medium influence value on Behavioral Intention.  That factor is the most influential in the application of M-learning in universities.